Oceanographic applications to eutrophication in tidal, coastal lagoons: the Ria Formosa, Portugal - Newton, Alice (2012)
Physical and biogeochemical processes control the impact of eutrophication in tidal, coastal lagoons and the ecosystem response to nutrient enrichment. Ascreening model of eutrophication in a tidal, coastal lagoon considers a well-mixed box, exchanging with the ocean at a daily rate determined by physical processes and converting nutrient to phytoplankton chlorophyll at a fixed yield. The model uses nutrient levels to estimate maximum biomass, that may be limited by light-controlled growth in turbid, turbulent, highly-diluted or heavily-grazed system. The components of the box model were tested using field data from the Ria Formosa, a mesotidal coastal lagoon in southern Portugal. Sampling coincided with equinox spring tides, in spring and autumn, as well as solstice neap tides, in summer and winter, to cover the full range of tidal exchange. Discrete sampling coincided with high water, mid-ebb, low water and mid-flood to exemplify the different tidal states. Sampling stations included the ocean boundary (lagoon inlet), and two different landward boundary situations: the shallow westernmost “blind end” of the lagoon, and one near to a major sewage outlets. Results show that nutrient loading in the Ria Formosa is sufficiently diluted and flushed by the tides to limit the effects of eutrophication in the outer lagoon. Flushing, however, is insufficient in the inner lagoon. In conclusion, basin-scale parameters in simple box models can be derived from detailed research models and the results of process studies to provide end-users with simple, transparent, screening models for eutrophication and related aspects of water quality.